Gugatan Class Action dalam Hukum Perlindungan Konsumen - Wiwik Sri Widiarty (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Abstract First time of the many cases that harm the interests of consumers as well as to the need for information and the development of knowledge in the field of law today is known as the class action, the Government, and Dewan Perwakilan Rakyat give attention to consumers in Indonesia. Provisions governing Class Action contained in Law No. 32 Year 2009 on Protection And Environmental Management, and Law No. 8 of 1999 on Consumer Protection, and also law PERMA No.1 Year 2002 on Proces Class Action. In order to demand justice for the consumer losses caused by the business, the consumer has the right to demand their rights as set out in the Consumer Protection Act, that the dispute mechanism can be chosen voluntarily by the parties to the dispute, namely through the courts or out of court. The class action suit is a civil lawsuit filed by a group of people who have an interest in a similar problem, either one or more of their members to sue or be sued as representative of the group without any members of the group are involved directly in the judicial process. In connection with this there is the benefit of a class action lawsuit in consumer disputes in court, but to fight for their rights, the principle litigants with simple, fast, and low cost, and the determinants that be a reason to be eligible class action, both in practice as well as in its implementation. Kata Kunci: Gugatan Class Action